Autonomy and Foreign Language Learning in a Virtual Learning Environment. - Hamilton, Miranda (Advances in digital language learning and teaching., 2013)
Digitalised learning with its promise of autonomy, enhanced learner choice, independence and freedom, is an intuitive and appealing construct but closer examination reveals it to be a rather simplistic proposition, raising the following questions.-What do we mean by autonomy? -What are we implying about the role of the teacher, the classroom, and interaction between learners? -What do we understand about the impact of technology on the ecology of the learning environment? This book describes the use of a Virtual Learning Environment (VLE) by a group of advanced English language learners in Me.